2016
DOI: 10.1002/slct.201601652
|View full text |Cite
|
Sign up to set email alerts
|

Protein Mimic Hydrophobicity Affects Intracellular Delivery but not Cargo Binding

Abstract: Protein transduction domain mimics (PTDMs) enable cellular uptake of macromolecular cargo such as proteins and nucleic acids. The presence of hydrophobic domains in PTDMs has been shown to enhance cargo uptake, but the role of hydrophobicity in PTDM‐binding of the desired cargo is not fully understood. Herein, block copolymer PTDMs composed of varying hydrophobic monomers were synthesized via ring‐opening metathesis polymerization (ROMP) to probe the effect that increasingly hydrophobic side chains had on bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(57 citation statements)
references
References 32 publications
2
55
0
Order By: Relevance
“…On first glance, this observation is surprising since, in general, the addition of a hydrophobic block increases CPPMs‘ delivery of cargo. [39,40,46,52] It is concievable that Poly-2 forms a stable microstructure in buffer that renders it unable to effectively interact with a protein that is large in comparison to siRNA. When taking previous reports into account, however, this is unlikely, as a hydrophobic block almost universally improves CPPM mediated protein uptake in cells regardless of microstructure character or micelle/vesicle size.…”
Section: Resultsmentioning
confidence: 99%
“…On first glance, this observation is surprising since, in general, the addition of a hydrophobic block increases CPPMs‘ delivery of cargo. [39,40,46,52] It is concievable that Poly-2 forms a stable microstructure in buffer that renders it unable to effectively interact with a protein that is large in comparison to siRNA. When taking previous reports into account, however, this is unlikely, as a hydrophobic block almost universally improves CPPM mediated protein uptake in cells regardless of microstructure character or micelle/vesicle size.…”
Section: Resultsmentioning
confidence: 99%
“…Givent hatb inding affinity seemed to be impacted by alterationsi nP TDMh ydrophobics egregation,amore recent study wasu ndertakeni nw hich theP TDMb lock architecture was maintained,b ut theh ydrophobic side chains were varied in an attempttomodulate theirEGFP bindingstrength. [34] Despitesignificant changest ot he PTDM hydrophobicity,a ll bindinga bilities were essentiallyt he same (Figure6a).H owever, thes imilarity in bindingw as notr eflectedi nt he resultso ft he delivery experimentsd oneu sing thes ameP TDMs.T hisr eporti ndicated that bindinga nd delivery aren ot necessarilyc orrelateda nd demonstrated that theoverall delivery landscapeiscomplex.…”
Section: Nicholasmentioning
confidence: 86%
“…Our group has developed and studied PTDMs capable of non‐covalently binding and delivering protein cargo into difficult‐to‐transfect cell lines . Most of this work has centered on chemically optimizing PTDMs through structure–activity relationships, and special attention has been given to optimizing the ratio of hydrophilic to hydrophobic monomers and the overall polymer hydrophobicity (Figure ) . Some of these same studies have featured cursory explorations of how polymer–protein binding impacts intracellular delivery.…”
Section: Polymer‐protein Binding Equilibrium and Deliverymentioning
confidence: 99%
See 2 more Smart Citations